Estudo farmacoquímico bioguiado pela atividade miorrelaxante do extrato etanólico das cascas do caule de Hymenaea courbaril L. (JATOBÁ) - Bezerra, Gabrieli da Penha (2013)
Hymenaea courbaril L. (Fabaceae), popularly known as "Jatoba", is used in folk medicine to treat respiratory diseases such as bronchitis and asthma. This study evaluated the effect of H. courbaril on the contractile of rat isolated trachea, as well as its potential antioxidant and anti-inflammatory, through an interdisciplinary study bioguided by myorelaxant activity of the ethanol extract from stem bark (EEHC). Chromatoghrafic fractionation of EEHC resulted in fractions of increasing polarity: hexane (HF), hexane:dichloromethane (HDF), dichloromethane (DF), dichloromethane:ethyl acetate (DEAF), ethyl acetate (EAF) and methanol (MF) fraction. EEHC, DF, DEAF, EAF and MF showed enhanced free radical scavenging in the DPPH test. EEHC, DF, DEAF and MF partially relaxed tracheal rings contracted with either CCh or K+, while EAF almost abolished such contractions. EAF was more potent to inhibit K+ than CCh-induced contractions. EAF reduced contractions that depended on divalent cation inflow through voltage-operated Ca2+ channels (VOCCs) or receptor-operated Ca2+ channels (ROCCs), but it was more potent to inhibit VOCC- than ROCC-dependent contraction in ACh-enriched Ca2+-free medium, indicating a preferential action in events mediated electromechanically. Oral pre-treatment of antigen-challenged animals with EAF prevented airways hyperresponsiveness on KCl-induced contractions and impaired the increase in the number of white cells, particularly eosinophils and neutrophils in bronchoalveolar lavage of these animals. Chemical investigation of the most bioactive fraction (EAF) was performed using chromatographic methods and 1H-NMR and 13C-NMR spectroscopic analysis, resulting in the isolation and identification of the flavonoid astilbin and oleanolic acid, a compound triterpenoid, which is isolated by the first time in Hymenaea. Astilbin showed myorelaxant activity on rat trachea rings contracted with K+, indicating that it may be partly responsible for the activity presented by EAF. This study provided scientific basis that H. courbaril presents potential antioxidant, anti-inflammatory and myorelaxant, which support its use in folk medicine to treat inflammatory airway diseases such as asthma.